\( \dfrac{x}{2}≥\dfrac{(5x-2)}{3}-\dfrac{(7x-3)}{5}\)

= \( \dfrac{x}{2}≥\dfrac{5(5x-2)-3(7x-3)}{15}\)

= \( \dfrac{x}{2}≥\dfrac{25x-10-21x+9}{15}\)

=\( \dfrac{x}{2}≥\dfrac{4x-1}{15}\)

= \(15x≥2(4x-1)\)

= \(15x≥8x-2\)

=\( 15x-8x≥8x-2-8x\)

= \( 7x≥-2\)

= \( x≥-\dfrac{2}{7}\)

The graphical representation of the solutions of the given inequality is as follows.

Answered by Abhisek | 1 year ago

Solve each of the following in equations and represent the solution set on the number line \( \dfrac{5x}{4}-\dfrac{4x-1}{3}>1,\) where x ϵ R.

Solve each of the following in equations and represent the solution set on the number line.\( \dfrac{5x-8}{3}\geq \dfrac{4x-7}{2}\), where x ϵ R.

Solve each of the following in equations and represent the solution set on the number line. 3 – 2x ≥ 4x – 9, where x ϵ R.

Solve each of the following in equations and represent the solution set on the number line. 3x – 4 > x + 6, where x ϵ R.

Solve each of the following in equations and represent the solution set on the number line. 5x + 2 < 17, where

**(i) **x ϵ Z,

**(ii)** x ϵ R.